Why all benefit when eefugees enjoy the EU's freedom of movement - Jeroen Doomernik (EconPol Forum, 2025)
It is unwise and unproductive to impose asylum regulations that do not fully consider the resources and ambitions of refugees. The 2016 Asylum and Migration Management Regulation (AMMR) does not solve the main problem: responsibilities lie with the country of first arrival. The new accelerated border regime on the EU's external borders is likely to fail or create serious human rights concerns. It would be wise to take the experiences with the Temporary Protection Directive (TPD) and its freedom of movement for Ukrainian refugees as best practice. Recognized refugees should immediately have the freedom of movement as enjoyed by EU nationals .
Keywords: 330